2020
DOI: 10.3390/ijerph17145083
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity Score: Implications for Obesity Prevention and Nutrient Adequacy in Renal Transplant Recipients

Abstract: Obesity affects both medical and surgical outcomes in renal transplant recipients (RTRs). Dietary diversity, an important component of a healthy diet, might be a useful nutritional strategy for monitoring patients with obesity. In this cross-sectional study, the data of 85 eligible RTRs were analyzed. Demographic data, routine laboratory data, and 3-day dietary data were collected. Participants were grouped into nonobesity and obesity groups based on body mass index (BMI) (for Asian adults, the cutoff point is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…A recent cross-sectional study in Bangladesh demonstrated that the serum creatinine level of newly diagnosed T2D was negatively correlated with the DDS (16). Furthermore, renal transplant patients with higher dietary diversity had a lower prevalence of obesity (17). The present case-control study is aimed to examine the association between DDS and the odds of DN among women with T2D in Semnan, Iran.…”
Section: Introductionmentioning
confidence: 92%
“…A recent cross-sectional study in Bangladesh demonstrated that the serum creatinine level of newly diagnosed T2D was negatively correlated with the DDS (16). Furthermore, renal transplant patients with higher dietary diversity had a lower prevalence of obesity (17). The present case-control study is aimed to examine the association between DDS and the odds of DN among women with T2D in Semnan, Iran.…”
Section: Introductionmentioning
confidence: 92%
“…Access to sufficient and nutritious food is a crucial factor for reducing food insecurity [ 5 , 6 ]. Efforts to ensure food security are related to socioeconomic factors and the level of information available regarding a healthy and balanced diet [ 7 , 8 ]. Particular sociodemographic factors are also related to the amount of consumption of foods such as fruits, vegetables and proteins, the consumption of which is related to the prevention of adverse health conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, although this was not a randomized controlled trial, our results were analyzed using reliable laboratory data, epidemiological methods, and various comprehensive tools and measures (e.g., 3-day dietary records with 24 h recall) to determine dietary quality. These methods have been used to assess the dietary intake of RTRs, examine their nutrition-related problems [32,37,50], and raise awareness about their nutritional status and CVD risk. Finally, the results are not generalizable to other areas of world where the diet may be different, and the small sample size precluded the examination of the interactions between nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to confirm dietary records, 24 h dietary recall was completed through face-to-face interviews by a well-trained dietitian. Dietary energy and nutrient intake were calculated using nutrition analysis software (Cofit Pro version 1.0.0, Cofit HealthCare Inc., Taipei, Taiwan) [32]. Macronutrient and micronutrient intakes were calculated according to guidelines presented in the database of the Taiwan MOHW [33].…”
Section: Dietary Intakementioning
confidence: 99%